Health, Happiness and the (Post) Human An Exploration of Biometrics, Biopolitics and the Body in Juli Zeh's The Method (2009) and Nicola Barker's H(a)ppy (2017). Issue 2 (2019) - Hinchcliffe, Jade
No abstract available